SISTEM PREDIKSI KEBAKARAN HUTAN MENGGUNAKANMETODE FUZZY LOGIC - Dea Fitriana (P3M Politeknik Negeri Bengkalis, 2025)
Forest and land fires are a serious problem that often occurs in Indonesia, especially duringthe dry season. The impact is very wide, ranging from ecosystem damage, health problems, to economiclosses. This research aims to design and build an Internet of Things (IoT)-based forest fire predictionsystem using the Fuzzy Logic method. The system is equipped with a temperature sensor (DHT22),smoke sensor (MQ-4), and flame sensor (Flame Sensor) connected to a ESP8266 NodeMCUmicrocontroller. The data collected by the sensors will be processed and analyzed using the Fuzzy Logicmethod to determine the level of fire risk with the categories of